2003
DOI: 10.1007/s00256-003-0689-y
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging for preoperative diagnosis and assessment of local tumor extent on localized giant cell tumor of tendon sheath

Abstract: This study confirms that MR imaging is able to depict the characteristic internal signal of GCTTS. Moreover, it can accurately assess the tumor size and degree of extent around the phalanx, which can affect the type of surgical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 21 publications
1
39
0
2
Order By: Relevance
“…On the T2WI, the signal intensities were equal to skeletal muscle in 2 patients, lower in 3 patients, slightly higher in 2 patients and more heterogeneous in 2 patients. Kitagawa et al (5) described the MRI features of 25 cases of L-GCTTS. The signal intensities of L-GCTTS that the authors observed were isointense to that of skeletal muscle or hyperintense on the T1WI; on the T2WI, the majority of signal intensities were hyperintense; and L-GCTTS enhanced following gadolinium administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the T2WI, the signal intensities were equal to skeletal muscle in 2 patients, lower in 3 patients, slightly higher in 2 patients and more heterogeneous in 2 patients. Kitagawa et al (5) described the MRI features of 25 cases of L-GCTTS. The signal intensities of L-GCTTS that the authors observed were isointense to that of skeletal muscle or hyperintense on the T1WI; on the T2WI, the majority of signal intensities were hyperintense; and L-GCTTS enhanced following gadolinium administration.…”
Section: Discussionmentioning
confidence: 99%
“…De Beuckeleer et al (4) identified that 10/13 cases of L-GCTTS exhibited highly homogeneous enhancement due to the presence of numerous proliferative capillaries in the collagenous stroma. Kitagawa et al (5) observed that 13/18 lesions were not homogeneously enhanced whereas 5 lesions exhibited homogeneous enhancement. In the present study involving 31 patients with L-GCTTS, on the T1WI the signal intensities of L-GCTTS were isointense in 26 patients and hypointense in 5 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic features being low signal intensity T1-and T2-weighted images, equal to that of skeletal muscle.8 MR imaging can accurately assess the tumour size and degree of extent around the phalanx, which can help in deciding the surgical approach. 9 Fine needle aspiration biopsy is used to clinch the tissue diagnosis preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Dans notre cas, il a objectivé un allongement de la conduction sensitive du nerf ulnaire à sa partie distale et une atteinte de la branche profonde motrice. L'IRM a un rôle prépondérant dans le diagnostic étiologique, elle permet de faire le diagnostic différentiel avec le sarcome des parties molles qui produit un signal d'intensité égale ou supérieure à celle de la graisse en T2, alors que les tumeurs à cellules géantes ont un signal entre le muscle et la graisse en T2 [13]. De plus, les tumeurs à cellules géantes se rehaussent après injection de Gadolinium du à la prolifération des capillaires dans le stroma, ce qui les différencient des kystes synoviaux [14].…”
Section: Issn: 2320-5407unclassified